(untitled) (Journal of Chittagong Medical College Teachers’ Association, 2009)
Key words: neurological examination; compressive myelopathy; MRI; myelomere; myelomelacia doi: 10.3329/jcmcta.v19i2.3864 Journal of Chittagong Medical College Teachers’ Association 2008: 19(2):12-15